Dosis de gallinaza y su influencia en las características agronómicas y rendimiento de, Momordica charantia L. "balsamina", en Zungarococha, Loreto. 2019 - Noriega Delgado, Fiorella (2021)
The experiment "Doses of gallinaza and its influence on the agronomic characteristics and yield of, Momordica charantia L. "balsamina", in Zungarococha, Loreto. 2019", was carried out in the facilities of the Workshop on Teaching and Research of Horticultural Plants (TEIPH), of the Faculty of Agronomy-UNAP, located at Km. 3 of the road to Zungarococha, south of the city of Iquitos, whose geographical coordinates are: South Latitude 03o 46´ 13.2¨ ; West Length 73o 22´ 10.4¨; Elevation: 126 meters above sea level. The type of research was experimental, explanatory with an independent variable (dose of hen) and six dependent variables (fruit/plant number, fruit length, fruit diameter, fruit weight, fruit/plant weight and fruit/ha weight), the objective of the research work was to determine the influence of hen doses on the agronomic characteristics and yield of, Momordica charantia L. "balsamina", in Zungarococha, Loreto. 2019" The experimental design used was the Completely Random Block Design, with four treatments and four repetitions. consisted of 2 rows, 4 floors/row and the sampling unit consisted of four plants/experimental unit. The results show that the doses of hen in Momordica charantia L. "balsamine", significantly influence agronomic characteristics and yield; where, the T2 Treatment (30 t of hen/ha), I present the best agronomic characteristics and yield, obtaining the best average values of fruit/plant number (57 fruits), fruit length (25 cm), fruit diameter (5.73 cm.), fruit weight (277 g.), fruit/plant weight (9.251 g.) and fruit/ha weight (37.01 t). the greatest economic benefit was obtained by the T2 Treatment (30 t of chicken / ha), with S /. 60,170.00